NSRG-23. 5-AMINOLEVULINIC ACID GUIDED RESECTION OF PAEDIATRIC CENTRAL NERVOUS SYSTEM TUMOURS: THE LARGEST SINGLE CENTRE SERIES IN THE UK. Issue 2 (22nd June 2018) - Burford, Charlotte; Kalyal, Nida; Pandit, Anand; Lavrador, Jose Pedro; Bleil, Cristina; Kailaya-Vasan, Ahilan; Zebian, Bassel
Abstract: BACKGROUND: 5-aminolevulinic acid (5-ALA, Gliolan) is widely used in adults for facilitating the resection of high-grade gliomas. However, its safety and efficacy in the paediatric population remains to be established. We present the UK's first case series of 10 patients, undergoing 11 operations with 5-ALA. METHODS: 10 consecutive patients (aged 1.6-15 years) underwent pre-operative administration of 20mg/kg of 5-ALA. The tumours were visualised intra-operatively under violet-blue light and the presence and usefulness of fluorescence was assessed. RESULTS: Strong fluorescence was observed in two WHO grade III ependymomas and a GBM (IV). Moderate fluorescence was seen in one pilocytic astrocytoma (I) and a pilomxyoid astrocytoma (II). Weak fluorescence was observed in a diffuse astrocytoma (II). The tumours types which showed no fluorescence included: a pilocytic astrocytoma, a glioneuronal tumour (II) and an anaplastic medulloblastoma (IV). No significant adverse drug reactions were recorded in any of the patients. CONCLUSIONS: Our case series adds to the evidence base supporting the safety of 5-ALA in the paediatric population. However, the diverse range of responses to 5-ALA in these tumours highlights the need for further trials into its usefulness in specific tumour types.